Method for adsorbing lead ions in water body by utilizing lepidolite smelting slag
By using lithium mica smelting slag as adsorption material, lead ions in wastewater are adsorbed in a water bath constant temperature shaker, the high cost of equipment for removing lead ions and secondary pollution risks in the prior art is solved, and efficient and economical wastewater is achieved The treatment reached a removal rate of 99.8%, which has environmental benefits and social value.
Patent Information
- Application Number
- CN202411470312.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art has problems such as high equipment cost, complex operation, potential secondary pollution risk and high operating costs when removing lead ions in wastewater, and the lithium mica smelting slag has not been used at a high value.
After drying, grinding and sieving the lithium mica smelting slag, it is added to lead-containing wastewater as an adsorption material, and adsorbs it in a water bath constant temperature shaker, thereby achieving the removal of lead ions.
It has achieved efficient removal of lead ions in wastewater, reduced treatment costs, reduced secondary pollution risks, solved the pollution of the ecological environment by lithium mica smelting slag storage and lead-containing wastewater discharge, and achieved a removal rate of 99.8%. Important environmental benefits and social values.
Smart Images

Figure CN119158534A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater heavy metal treatment, in particular to a method for utilizing lepidolite smelting slag to absorb lead ions in water. Background Art
[0002] Lead ions contained in wastewater are toxic heavy metal ions that pose serious hazards to human health and the ecological environment. Removing lead ions from wastewater is one of the important tasks of environmental protection and water resource reuse. Traditional treatment methods for lead-containing wastewater mainly include chemical precipitation, membrane separation, ion exchange and adsorption. Although the chemical precipitation method has simple equipment and convenient operation, it is accompanied by high costs, large amounts of sludge generation and potential secondary pollution risks; the advantages of the membrane separation method are simple equipment, convenient operation, high adsorption efficiency, and the treated water is reusable, but the cost is too high and the stability of the membrane material is poor. The ion exchange method can treat large-volume lead-containing wastewater without secondary pollution, but its reaction cycle is long and the operating cost is high. The adsorption method has significant advantages in terms of ease of operation, high efficiency and cost-effectiveness, and has gradually become the focus of research. The adsorption method can not only effectively remove lead ions from wastewater, but also reduce treatment costs and complex operation links, providing a more economical and environmentally friendly solution for the treatment of lead-containing wastewater.
[0003] As an important mineral raw material for extracting lithium, lithium mica produces a large amount of smelting slag during the smelting process. The lithium mica smelting slag is abundant in resources and low in cost. Its particles are fine, the specific surface area is relatively large, and it has a porous structure. In addition, the lithium mica smelting slag contains a large number of active ingredients (such as SiO 2 、Al 2 O 3 etc.), which makes it have potential adsorption capacity. At present, the application of lithium mica smelting slag is mainly used in the production of traditional building materials including cement and concrete, and the preparation of geopolymer cementitious materials, and it cannot be used at a high value. Compared with traditional lead-containing wastewater treatment methods, such as chemical precipitation method, ion exchange method, etc., the use of lithium mica smelting slag as an adsorption material to remove lead ions in water bodies does not require the addition of additional chemical reagents. The operation is simple and reduces the risk of secondary pollution. The use of lithium mica smelting slag to adsorb lead ions in water bodies solves the pollution of the ecological environment caused by the storage of lithium mica smelting slag and the discharge of lead-containing wastewater, and truly realizes the circular economy goal of "waste recycling and waste treatment". Summary of the invention
[0004] In order to solve the above technical problems existing in the prior art, the embodiment of the present invention provides a method for adsorbing lead ions in water using lepidolite smelting slag. The technical solution is as follows:
[0005] S1, drying the lithium mica smelting slag to remove the moisture contained therein;
[0006] S2, the dried lithium mica smelting slag is ground and sieved to -100 mesh accounting for 100%, to obtain adsorption material, stand-by;
[0007] S3, adding the adsorbent material obtained in step S2 into the lead ion-containing wastewater, placing it in a water bath constant temperature shaker for adsorption;
[0008] S4, filtering the solution after adsorption in step S3 to obtain purified wastewater.
[0009] In the step S1, the lepidolite smelting slag is dried to a moisture content not exceeding 0.1%.
[0010] The lead ion concentration in the lead ion-containing wastewater in step S3 is 600-3000 mg / L.
[0011] In the step S3, the solid-liquid ratio of the mass (g) of the adsorption material to the volume (L) of the lead-containing wastewater is 5:1 to 20:1.
[0012] In step S3, the temperature of the water bath constant temperature shaker is 20-60° C., and the rotation speed is 250 r / min.
[0013] In the step S3, the adsorption is performed by shaking in a water bath constant temperature shaker for 60 to 120 minutes.
[0014] The content of lead ions in the purified wastewater obtained in step S4 is less than 0.5 mg / L.
[0015] The beneficial effects brought about by the technical solution provided by the embodiment of the present invention include at least:
[0016] In the above scheme, the adsorption material used is low-priced and has a good adsorption effect. No additional chemical reagents need to be added during the adsorption process. The operation is simple and the risk of secondary pollution is reduced. The use of lithium mica smelting slag to adsorb lead ions in water bodies solves the pollution of the ecological environment caused by the storage of lithium mica smelting slag and the discharge of lead-containing wastewater. The present invention utilizes lithium mica smelting slag, which is dried, ground and screened to efficiently adsorb lead ions in wastewater (in the prepared lead ion solution, the removal rate of lead ions can reach 99.8%), which has important environmental benefits and social value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 It is the XRD diagram of the lithium mica smelting slag in the embodiment of the present invention. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is described below in conjunction with specific embodiments.
[0020] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0021] In the embodiments of the present invention, sometimes the subscripts such as W 1 It may be written in non-subscript form such as W1. When the difference is not emphasized, the meaning is the same.
[0022] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.
[0023] The embodiment of the present invention provides a method for adsorbing lead ions in water using lepidolite smelting slag, comprising the following steps:
[0024] S1, drying the lithium mica smelting slag to remove the moisture contained therein;
[0025] S2, the dried lithium mica smelting slag is ground and sieved to -100 mesh to obtain adsorption material, stand-by;
[0026] S3, adding the adsorbent material obtained in step S2 into the lead ion-containing wastewater, placing it in a water bath constant temperature shaker for adsorption;
[0027] S4, filtering the solution after adsorption in step S3 to obtain purified wastewater.
[0028] The main components of the lithium mica smelting slag are shown in Table 1, and the physical results are shown in Figure 1 .
[0029] Table 1 Main components of lepidolite smelting slag (%)
[0030]
[0031] The concentration of lead ions remaining in the filtrate of the purified wastewater obtained in step S4 is measured by inductively coupled plasma optical emission spectrometry (ICP-OES). The removal rate of heavy metal ions by the adsorbent is calculated according to the following formula (1). The adsorption capacity of heavy metal ions is calculated according to the following formula (2).
[0032] (1)
[0033] (2)
[0034] Where: R-lead ion removal rate;
[0035] q-adsorption capacity of adsorbent material for lead ions (mg / g);
[0036] - Initial lead ion concentration (mg / L);
[0037] c-residual lead ion concentration after adsorption (mg / L);
[0038] v-volume of lead ion solution (L);
[0039] m-mass of adsorbent material added (g).
[0040] This will be described below with reference to specific embodiments.
[0041] Example 1
[0042] The prepared lithium mica smelting slag adsorption material was put into 50 mL of lead ion solution with an initial concentration of 600 mg / L, and the amount of adsorption material was 0.5 g. It was adsorbed for 120 minutes at a temperature of 25°C and a speed of 250 r / min in a water bath constant temperature shaker, and the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometer. The results showed that the lead ion removal rate was 99.82% and the adsorption capacity was 59.89 mg / g.
[0043] Example 2
[0044] The prepared lithium mica smelting slag adsorption material was put into 50 mL of lead ion solution with an initial concentration of 700 mg / L, and the amount of adsorption material was 0.5 g. After adsorption for 120 minutes at a temperature of 25°C and a speed of 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.74% and the adsorption capacity was 69.82 mg / g.
[0045] Example 3
[0046] The prepared lithium mica smelting slag adsorption material was put into 50 mL of lead ion solution with an initial concentration of 800 mg / L, and the amount of adsorption material was 0.5 g. After adsorption for 120 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.62% and the adsorption capacity was 79.70 mg / g.
[0047] Example 4
[0048] The prepared lithium mica smelting slag adsorption material was put into 50 mL of lead ion solution with an initial concentration of 900 mg / L, and the amount of adsorption material was 0.5 g. After adsorption for 120 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.58% and the adsorption capacity was 89.62 mg / g.
[0049] Example 5
[0050] The prepared lithium mica smelting slag adsorption material was put into 50 mL of lead ion solution with an initial concentration of 1000 mg / L, and the amount of adsorption material was 0.5 g. After adsorption for 120 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.47% and the adsorption capacity was 99.47 mg / g.
[0051] Example 6
[0052] The prepared lithium mica smelting slag adsorption material was put into 100 mL of lead ion solution with an initial concentration of 1000 mg / L, and the amount of adsorption material was 2.0 g. After adsorption for 60 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.94% and the adsorption capacity was 50.00 mg / g.
[0053] Example 7
[0054] The prepared lithium mica smelting slag adsorption material was put into 100 mL of lead ion solution with an initial concentration of 2000 mg / L. The amount of adsorption material was 2.0 g. After adsorption for 60 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.87% and the adsorption capacity was 99.87 mg / g.
[0055] Example 8
[0056] The prepared lithium mica smelting slag adsorption material was put into 100 mL of lead ion solution with an initial concentration of 3000 mg / L, and the amount of adsorption material was 2.0 g. After adsorption for 60 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 94.07% and the adsorption capacity was 141.10 mg / g.
[0057] Example 9
[0058] The prepared lithium mica smelting slag adsorption material was put into 100 mL of lead ion solution with an initial concentration of 1000 mg / L, and the amount of adsorption material was 0.8 g. After adsorption for 60 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 97.83% and the adsorption capacity was 122.29 mg / g.
[0059] Example 10
[0060] The prepared lithium mica smelting slag adsorption material was put into 100 mL of lead ion solution with an initial concentration of 1000 mg / L, and the amount of adsorption material was 1.0 g. After adsorption for 60 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.37% and the adsorption capacity was 99.37 mg / g.
[0061] Embodiment 11
[0062] The prepared lithium mica smelting slag adsorption material was put into 100 mL of lead ion solution with an initial concentration of 1000 mg / L. The amount of adsorption material was 1.3 g. After adsorption for 60 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.81% and the adsorption capacity was 76.78 mg / g.
[0063] Example 12
[0064] The prepared lithium mica smelting slag adsorption material was put into 100 mL of lead ion solution with an initial concentration of 1000 mg / L, and the amount of adsorption material was 1.5 g. After adsorption for 60 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.76% and the adsorption capacity was 66.51 mg / g.
[0065] Example 13
[0066] The prepared lithium mica smelting slag adsorption material was put into 100 mL of lead ion solution with an initial concentration of 1000 mg / L, and the amount of adsorption material was 2.0 g. After adsorption for 60 minutes at 25°C and 250 r / min in a water bath constant temperature shaker, the residual lead ion content in the solution was measured by inductively coupled plasma emission spectrometry. The results showed that the lead ion removal rate was 99.88% and the adsorption capacity was 49.94 mg / g.
[0067] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for adsorbing lead ions in water using lepidolite smelting slag, characterized in that: The method comprises: S1, drying the lithium mica smelting slag; S2, the lepidolite smelting slag after drying in step S1 is ground and sieved to -100 mesh accounting for 100%, to obtain an adsorption material for standby use; S3, adding the adsorbent material obtained in step S2 into the lead ion-containing wastewater, placing it in a water bath constant temperature shaker for adsorption; S4, filtering the solution after adsorption in step S3 to obtain purified wastewater.
2. The method for adsorbing lead ions in water using lepidolite smelting slag according to claim 1, characterized in that: In the step S1, the lepidolite smelting slag is dried to a moisture content not exceeding 0.1%.
3. The method for adsorbing lead ions in water using lepidolite smelting slag according to claim 1, characterized in that: The lead ion concentration in the lead ion-containing wastewater in step S3 is 600-3000 mg / L.
4. The method for adsorbing lead ions in water using lepidolite smelting slag according to claim 1, characterized in that: In step S3, the solid-liquid ratio of the mass of the adsorption material to the volume of the lead-containing wastewater is 5:1 to 20:
1.
5. The method for adsorbing lead ions in water using lepidolite smelting slag according to claim 1, characterized in that: In step S3, the temperature of the water bath constant temperature shaker is 20-60° C., and the rotation speed is 250 r / min.
6. The method for adsorbing lead ions in water using lepidolite smelting slag according to claim 1, characterized in that: In the step S3, the adsorption is performed by shaking in a water bath constant temperature shaker for 60 to 120 minutes.
7. The method for adsorbing lead ions in water using lepidolite smelting slag according to claim 1, characterized in that: The lead ion content in the purified wastewater obtained in step S4 is less than 0.5 mg / L.
Citation Information
Patent Citations
Preparation method of lithium slag adsorbent for liquid extraction of lithium
CN103706325A
Preparation method of lithium slag adsorbent
CN107324438A
High-performance ion exchange type adsorbent, preparation and application to extraction of rubidium / lithium
CN108479719A
Preparation method and application of adsorbent for efficiently removing heavy metal ions in wastewater based on electrolytic manganese residues
CN111939868A
Porous adsorbent prepared from lithium ore waste residues and used for heavy metals in wastewater and preparation method of porous adsorbent
CN114887587A
Cited By
Method for preparing heavy metal repair material from lepidolite lithium extraction waste residue, heavy metal repair material and application
CN121892077A
